2014
DOI: 10.1002/app.40697
|View full text |Cite
|
Sign up to set email alerts
|

Study on effects of short glass fiber reinforcement on the mechanical and thermal properties of PC/ABS composites

Abstract: This article mainly investigated the length distributions of the alkali-free short glass fibers in specimens and their effect on the mechanical and thermal properties of the composites. The results show that the initial length, addition level and feed way of the fibers have obvious effects on the length distributions of fibers in specimens, and thereby the mechanical and thermal properties of the composites. The main-direction feed way has an intense shear action on the fibers in specimens. With the increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, for most of the composites with short reinforcing fibers, the impact strength only shows an improvement by 10-20% in comparison to their pure resins due to the distribution of the residual in the range of 0.1-0.5 mm as reported by the corresponding literature. [40][41][42]47,48 The high levels of impact strength exhibited by the LFT composites are often attributed to energy dissipating mechanisms of fiber debonding, pullout, and fracture, which have been discussed by many researchers. [18][19][20][21] The impact energy dissipation is also generally influenced by several factors including matrix fraction, fiber debonding, friction between the interfaces of matrix and fibers, fiber pullout, and fiber breakage.…”
Section: Mechanical Properties and Fiber Length Distributionmentioning
confidence: 99%
“…However, for most of the composites with short reinforcing fibers, the impact strength only shows an improvement by 10-20% in comparison to their pure resins due to the distribution of the residual in the range of 0.1-0.5 mm as reported by the corresponding literature. [40][41][42]47,48 The high levels of impact strength exhibited by the LFT composites are often attributed to energy dissipating mechanisms of fiber debonding, pullout, and fracture, which have been discussed by many researchers. [18][19][20][21] The impact energy dissipation is also generally influenced by several factors including matrix fraction, fiber debonding, friction between the interfaces of matrix and fibers, fiber pullout, and fiber breakage.…”
Section: Mechanical Properties and Fiber Length Distributionmentioning
confidence: 99%
“…WPCs fire retardancy is critical, because most WPCs are quite highly flammable. Although domestic and foreign scholars have conducted a wealth of research work on the antistatic properties of virgin plastic [4][5][6][7][8][9] and the fire retardancy of WPCs [10][11][12][13][14][15][16][17][18][19][20], relatively limited academic research exists on WPCs antistatic properties combined with fire retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of each reinforcing agent, the overall impact toughness and tensile strength increased in the first place and decreased afterwards, and the reinforcing function of carbon fibers was more significant. Wang et al [4] found that the mechanical properties of composite was dependent on the fiber content in the composite: with the increase of fiber content, the tensile strength and flexural strength increased while the impact strength firstly decreased and then maintained constant. Nayak et al [5] reported that when fiber content exceeded a critical value, the fiber in composite material products would agglomerate, resulting in voids inside the materials.…”
Section: Current Work On Properties Of Fiber-reinforced Injection-molmentioning
confidence: 99%